Ultrasound-targeted microbubble destruction optimized HGF-overexpressing bone marrow stem cells to repair fibrotic liver in rats - Ting Sun; Hualin Li; Yun Bai; Min Bai; Feng Gao; Jie Yu; Rong Wu; Lianfang Du; Fan Li (Stem Cell Research & Therapy, 2020)
Abstract Background/aims Bone marrow mesenchymal stem cells (BMSCs) have shown their therapeutic potential in cytotherapy for liver fibrosis. However, the insufficient homing of BMSCs and undefined proliferation of BMSCs represent a significant challenge and largely limit the effective implementation. The aims of the present study were to determine whether stable expression of hepatic growth factor (HGF) in BMSCs coupled with ultrasound-targeted microbubble destruction (UTMD) technique could effectively and definitely alleviating carbon tetrachloride (CCl4)-induced liver fibrosis in rats. Materials and methods A rat model of liver fibrosis was acquired by injection of carbon tetrachloride (CCl4). The experimental rats were randomly assigned to the four groups: normal, CCl4, BMSCs-HGF/US, and BMSCs-HGF/UTMD groups. The BMSCs, transfected by recombinant adeno-associated virus vector encoding human genome sequence of HGF (BMSCs-HGF), were transplanted in rat via the tail vein. The homing efficiency of BMSCs was observed by immunofluorescence staining. The liver function and its morphological changes were analyzed by biochemical tests and liver histology. The expression of liver fibrosis markers including α-smooth muscle actin (α-SMA), collagen I, and vimentin were examined by immunohistochemistry and quantitative real-time polymerase chain reaction. Results The homing efficiency of BMSCs in the fibrotic liver was significantly greater with the application of UTMD. The biochemical markers of liver function and histopathological results showed significantly better improvement in BMSCs-HGF/UTMD group than the other groups, and the serum levels of biochemical markers returned to normal ranges in 12 weeks in this group. Furthermore, the expression levels of liver fibrosis markers (α-SMA, collagen I, and Vimentin) were all significantly lower in BMSCs-HGF/UTMD group in comparison with other groups. Conclusions Our findings have demonstrated that stable expression of HGF in BMSCs and application of the UTMD technique facilitate the homing of BMSCs, and more importantly, which could further improve their alleviation of liver fibrosis. Therefore, these findings have an important clinical implication that AAV-BMSCs-HGF and UTMD hold promise as a novel therapeutic approach for liver fibrosis.